Uwarunkowania i kanały finansowania rolnictwa w Polsce - Zawojska, Aldona (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The paper presents specific conditions for agriculture financing and main obstacles to the development of agricultural and rural financial services. One of those obstacles are sectoral correlated and covariant risks, so development of traditional and introduction of innovative instruments to protect farmers and financial institutions from some of those risks can stimulate the supply of rural and agricultural financing. It is also suggested that in order to overcome general under-supply of finance for agricultural activities and to rural households, microfinance institutions and both direct and indirect value chain finance should be supported